Coral Skeletal Luminescence Records Changes in Terrestrial Chromophoric Dissolved Organic Matter in Tropical Coastal Waters. Issue 8 (28th April 2021) - Kaushal, Nikita; Sanwlani, Nivedita; Tanzil, Jani T. I.; Cherukuru, Nagur; Sahar, Syamil; Müller, Moritz; Mujahid, Aazani; Lee, Jen N.; Goodkin, Nathalie F.; Martin, Patrick
Abstract: Terrigenous dissolved organic matter (tDOM) carried by rivers represents an important carbon flux to the coastal ocean, which is thought to be increasing globally. Because tDOM is rich in light‐absorbent chromophoric dissolved organic matter (CDOM), it may also reduce the amount of sunlight available in coastal ecosystems. Despite its biogeochemical and ecological significance, there are few long‐term records of tDOM, hindering our understanding of its drivers and dynamics. Corals incorporate terrestrial humic acids, an important constituent of CDOM, resulting in luminescent bands that have been previously linked to rainfall and run‐off. We show that luminescence green‐to‐blue (G/B) ratios in a coral core growing in waters affected by peatland run‐off correlate strongly with remote sensing‐derived CDOM absorption. The 24‐year monthly resolution reconstructed record shows that rainfall controls land‐to‐ocean tDOM flux from this protected peatland catchment, and suggests an additional impact by solar radiation, which degrades tDOM at sea. Plain Language Summary: A critical priority in biogeochemistry is to improve our understanding of the global carbon cycle so that we can make accurate predictions of future CO2 concentrations. One important but still enigmatic aspect of the carbon cycle is the transport and fate of organic carbon from soils to the ocean. Our understanding of this flux is particularly limited by the lack of historical time‐series measurements. One way of obtaining such historical data is through satellite‐derived measurements, but this can only yield data for the most recent decades. Here, we show that historical records of terrestrial carbon can also be reconstructed from luminescence measurements of coral cores, which have the potential to yield centuries‐long time series of carbon concentrations. Corals are carbonate archives that record different environmental parameters during their skeleton formation. Luminescence is caused by the incorporation of humic acids, an integral component of terrestrially derived dissolved organic carbon. Our 24‐year long reconstruction from a coral core collected off Borneo suggests that organic carbon concentrations are driven by rainfall over adjacent peatlands, and by solar radiation that breaks down the organic carbon at sea. There is no long‐term shift, suggesting that this peatland catchment has stayed protected from land‐use change. Key Points: We show that luminescence in coral skeletons is a proxy for terrestrial chromophoric dissolved organic matter (CDOM) This proxy yields information on land‐to‐ocean dissolved organic matter (DOM) flux in historically under‐sampled tropical seas A 24‐year reconstructed CDOM record from Borneo shows large seasonal DOM flux from peatland, and likely influences of photodegradation